Experienced inequality in the social media structures – a feminist perspective : Uncovering the gender inequality of social media platforms - Kokkomäki, Venla (My University, 2022)
In marketing research, social media has been a topic of interest since its early days of existence. The social networking sites are nowadays formed as platforms that facilitate critical activities for businesses, organizations and societies. Furthermore, the platforms have penetrated into people’s lives, providing or limiting the possibilities to function in our society. The social media companies have tremendous power in users’ lives, but yet it is unclear who’s goals are prioritized in these platforms and whose are not. Surprisingly, only little of the social media studies have focused on how the platforms are structured and thus, this study addressed the issue. This research aimed to answer this research gap by gaining an understanding of the experienced inequality in social media structures through taking a feminist perspective. Feminist perspective in this study referred to the idea that social medias made by humans cannot be value-free nor objective. Thus, the analysis for inequality must regard the biases of our society. The empirical study in this thesis was conducted as qualitative research and in two parts: first conducting a content analysis to further define the social media structures and then studying the experienced inequality by individual interviews. The study followed an abductive study as it combined earlier theories from platform structures, feminist theories regarding online spaces and user experiences on social media, and finally combing it with the knowledge gathered from the empirical study. The study results indicated that the experience of inequality in the social media structures was common across different genders and races, but the experiences of inequality are more intense and personal on gender minority users and people of colour. The social media structures defined in this study were affordances, algorithms and content moderation. The central findings were that on gender minority participants the experience of alienation was highlighted but the feeling of unsafety on the platforms was universal . The study produced valuable gender and race sensitive data for the purpose of developing social media platforms more equal.

Sosiaalisen median alustat ovat olleet markkinoinnin tutkimuksen kohteena aivan niiden syntyhetkistä lähtien. Nykypäivänä sosiaalisten medioiden rooli on merkittävä niin yritystoiminnan, yhteiskunnallisen keskustelun kuin ihmisten välisen yhteydenpidon kannalta. Alustoilla on siis kasvava valta yhteiskuntamme rakenteissa. Viime vuosina on kuitenkin herännyt kysymys tämän vallan käytöstä ja sen jakautumisesta – kenen etuja sosiaaliset mediat ajavat ja kenen eivät. Aikaisemmassa tutkimuksessa epätasa-arvon kokemukset sekä ei-binäärinen tieto ovat jääneet vähemmälle huomiolle liittyen sosiaalisten medioiden käyttökokemuksiin. Tämä tutkielma vastasi tutkimusaukkoon pyrkimällä ymmärtämään epätasa-arvon kokemuksia sosiaalisen median rakenteissa feministisen perspektiivin kautta. Feministinen perspektiivi tässä tutkielmassa tarkoitti periaatetta, että sosiaalisen median alustat heijastelevat yhteiskunnassamme vallitsevia vinoumia, mikä tulee tutkimuksessa ottaa huomioon. Empiirinen tutkimus suoritettiin kahdessa vaiheessa: ensin tutkimalla sosiaalisen median rakenteita sisältöanalyysin kautta ja seuraavaksi keräämällä aineistoa yksilöhaastatteluista. Tutkielma seurasi abduktiivisen tutkimuksen periaatteita verraten aikaisempaa teoriaa uuteen kerättyyn aineistoon. Tutkimuksen tulokset valottivat, että monet sukupuolet sekä etnisyydet kokivat epätasa-arvoa sosiaalisen medioiden rakenteissa, mutta epätasa-arvon kokemukset olivat intensiivisempiä sekä henkilökohtaisempia sukupuolivähemmistöillä sekä ei-valkoisilla sosiaalisen median käyttäjillä. Rakenteet, joita tämä tutkielma analysoi olivat käyttömahdollisuudet, algoritmit sekä sisällön moderointi. Yksi keskeisimmistä löydöksistä oli, että sukupuolivähemmistöillä nämä rakenteet aiheuttivat vieraantumisen sekä ulkopuolisuuden tunnetta, mutta turvattomuuden tunne oli yhteinen eri sukupuolille sekä etnisyyksille. Tämä tutkielma tuotti arvokasta sukupuolieriteltyä tietoa kokemuksista sosiaalisen median alustojen rakenteissa sekä nosti esiin alustojen kehityskohteita.
Keywords: social media, feminist perspective, user experience